Dance Video Creation as an Arts-Based Learning Practice:The Role of Self-Efficacy, Emotion, and Narcissistic Tendencies in Elementary Dance Education - Chen, Kuan-Wei (Universitas Negeri Semarang, 2025)
This study examines dance video creation as an arts-based learning practice in elementary dance education, focusing on how self-efficacy, emotional experience, and narcissistic tendencies shape students’ creative engagement. Positioned within arts education, the study explores the interaction between psychological traits and embodied artistic processes in dance learning. Data were collected from 37 elementary school students participating in a dance program in Taipei, Taiwan. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study analyzed relationships among narcissistic tendencies, creative self-efficacy, perceived value of creating, and positive and negative emotions during dance video production. The results show that narcissistic tendencies positively influence self-efficacy, while higher self-efficacy is associated with a lower perceived value of the creative process. Self-efficacy enhances positive emotions, whereas a higher perceived value of creating intensifies negative emotions, indicating creative tension inherent in arts-based learning. These findings highlight dance video creation as a pedagogical space where emotional experience, artistic exploration, and learning processes intersect, offering insights for designing reflective and process-oriented dance education.